Acute hospital administration of amiodarone and/or lidocaine in shockable patients presenting with out-of-hospital cardiac arrest: A nationwide cohort study. (15th January 2017) - Huang, Chien-Hua; Yu, Ping-Hsun; Tsai, Min-Shan; Chuang, Po-Ya; Wang, Tzung-Dau; Chiang, Chih-Yen; Chang, Wei-Tien; Ma, Matthew Huei-Ming; Tang, Chao-Hsiun; Chen, Wen-Jone
Abstract: Background: Terminating ventricular fibrillation (VF) or pulseless ventricular tachyarrhythmia (VT) is critical for successful resuscitation of patients with shockable cardiac arrest. In the event of shock-refractory VF, applicable guidelines suggest use of anti-arrhythmic agents. However, subsequent long-term outcomes remain unclear. A nationwide cohort study was therefore launched, examining 1-year survival rates in patients given amiodarone and/or lidocaine for cardiac arrest. Methods: Medical records accruing between years 2004 and 2011 were retrieved from the Taiwan National Health Insurance Research Database (NHIRD) for review. This repository houses all insurance claims data for nearly the entire populace (> 99%). Candidates for study included all non-traumatized adults receiving DC shock and cardiopulmonary resuscitation immediately or within 6 h of emergency room arrival. Analysis was based on data from emergency rooms and hospitalization. Results: One-year survival rates by treatment group were 8.27% (534/6459) for amiodarone, 7.15% (77/1077) for lidocaine, 11.10% (165/1487) for combined amiodarone/lidocaine use, and 3.26% (602/18, 440) for use of neither amiodarone nor lidocaine (all, p < 0.0001). Relative to those given neither medication, odds ratios for 1-year survival via multiple regression analysis were 1.84 (95% CI: 1.58–2.13; p < 0.0001) for amiodarone, 1.88 (95% CI: 1.40–2.53; p < 0.0001) for lidocaine, and 2.18 (95% CI: 1.71–2.77; p < 0.0001) for dual agent use. Conclusions: In patients with shockable cardiac arrest, 1-year survival rates were improved with association of using amiodarone and/or lidocaine, as opposed to non-treatment. However, outcomes of patients given one or both medications did not differ significantly in intergroup comparisons.